Development student worksheets to enhance computational thinking skills in 7th grade students on ratio material - Mustaqimah, Utami Puspita Sabilla; Supratman, Supratman; Lestari, Puji (UNION : Jurnal Ilmiah Pendidikan Matematika, 2024)
Computational thinking is a theory born in computer science that applies computational principles to solve a problem. It is a new concern in the PISA 2021 mathematical assessment to accommodate human resources needs that can compete in the 21st-century digitalization era. This study aims to develop a learning tool called student worksheet (LKPD) that integrates indicators of computational thinking skills into the material ratio. The method used is Research and Development (R&D), with the subject of research being 32 students in one Junior High School in Ciamis Regency. The data collection technique is done by observation, interview, and questionnaire given to material experts, media experts, and students. The data were analyzed quantitatively using descriptive product validity and practicality scores. The results showed that the assessment of material experts, including aspects of legality and morality, the feasibility of content, the feasibility of presentation, and aspects of computational thinking, received a level of validity of 99%, so it is included in the category of very valid. Likewise, the assessment of media experts covering anatomy, graphics, and use of language was declared very valid, with a validity rate of 82 %. The product's practicality gets a very practical category with an average score of 86% covering material aspects, use of language, interest, and aspects of computational thinking. The products that have been developed are considered valid and practical for use as educational resources for learning ratios and enhancing computational thinking ability.